A More Excellent Way: Philip Melanchthon’s Corinthians Lectures of 1521–22 - Weaver, William P. (Renaissance and Reformation / Renaissance et Réforme)

(untitled) (Iter Press, 2014)
Through a critical study of Philip Melanchthon’s 1521–22 lectures on 1 and 2 Corinthians, this essay evaluates his rhetorical method of reading and annotating Scripture. Building on a conventional analogy between ad fontes and sola scriptura, it investigates an equally operative analogy between consuetudo (linguistic usage) and what Melanchthon called the sermo or mos Scripturae, the “speech” or “usage of Scripture.” As a guide to the mos Scripturae, the early Corinthians lectures are an indispensable complement to his contemporary annotations on Romans. They reveal his attempt to integrate Luther’s “theology of the cross” into a theory of learned reading and shed light on the composition of the first systematic theology of the Lutheran faith, the Loci Communes, also published in 1521. Taken together as speeches, Paul’s letters to the Corinthians are unique enunciations of law and gospel, and unique examples of the “discourse of the cross.”